A polymer modified positive electrode sheet and preparation method thereof, and a lithium battery

By forming a 3D cross-linking network on the positive electrode sheet of the lithium battery, and modifying the positive electrode sheet with unsaturated phosphonate polymerizable monomers, the problem of the risk of thermal runaway in the lithium battery is solved and the thermal safety and electrochemical performance of the battery are improved.

CN115692606BActive Publication Date: 2025-03-14JIANGSU WEILAN NEW ENERGY BATTERY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211522341.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-30
Publication Date
2025-03-14
Estimated Expiration
2042-11-30

AI Technical Summary

Technical Problem

The prior art is difficult to effectively reduce the risk of thermal runaway in liquid lithium batteries and solid lithium batteries, especially under high-capacity positive electrodes and high temperature conditions, resulting in limited battery safety.

Method used

The polymer-modified positive electrode sheet is prepared by using unsaturated phosphonate polymerizable monomers. By forming a 3D cross-linking network on the surface of the positive electrode sheet or the gap between the active material, the thermal stability and lithium ion conduction performance of the positive electrode are improved.

Benefits of technology

It effectively reduces the exothermic reaction of lithium batteries in the early stage of thermal runaway, improves the thermal safety and electrochemical performance of the batteries, and is suitable for liquid and solid lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115692606B_ABST
    Figure CN115692606B_ABST
Patent Text Reader

Abstract

The present invention discloses a polymer-modified positive electrode plate and a preparation method thereof, and a lithium battery. The polymer-modified positive electrode plate comprises a cross-linked phosphonate polymer, a positive electrode active material, a positive electrode adhesive and a conductive additive. The cross-linked phosphonate polymer forms a 3D cross-linked network on the surface of the positive electrode plate and / or in the gap between the positive electrode active materials; the cross-linked phosphonate polymer is obtained by coating an unsaturated phosphonate polymerizable monomer on the surface of the positive electrode plate, or mixing an unsaturated phosphonate polymerizable monomer in a positive electrode plate slurry and forming a plate, and then completing in-situ polymerization and cross-linking during the baking process of the plate. The present invention also proposes a preparation method for the modified positive electrode plate and a lithium battery using the same. The modified positive electrode plate and lithium battery provided by the present invention have significantly improved safety and stable electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a polymer-modified positive electrode plate and a preparation method thereof, and a lithium battery. Technical Background

[0002] Liquid batteries are a new type of high-energy battery successfully developed in the 20th century. They have the advantages of high energy, high battery voltage, wide operating temperature range, and long storage life. However, thermal runaway is inevitable in liquid batteries, which endangers battery safety and limits the performance of liquid batteries. Thermal runaway is a chain reaction, which is generally believed to start with the rupture of the negative electrode / electrolyte interphase (SEI), followed by the redox reaction between the negative electrode and the electrolyte, the rupture of the positive electrode / electrolyte interphase (CEI), the redox reaction between the positive electrode and the electrolyte, and the redox reaction between the positive electrode and the negative electrode. Especially for high-capacity positive electrodes, they produce more oxygen-containing free radicals and oxygen at high temperatures, and produce violent redox reactions with the electrolyte or the negative electrode. They are the main heat source for thermal runaway of the battery, resulting in an increased risk of thermal runaway.

[0003] In the prior art, the technical means for reducing the risk of thermal runaway include improving the electrolyte / electrolyte and improving the positive electrode. For example, patent CN107785609B proposes to mix terminal unsaturated methyl phosphonate oligomers, free radical initiators, lithium salts, and battery additives in a certain proportion, and then in situ polymerize and solidify them into a completely non-flammable all-solid electrolyte under heating conditions. However, this method cannot be applied to liquid batteries, and the ionic conductivity of the all-solid electrolyte itself is lower than that of the liquid electrolyte at room temperature. The introduction of flame retardant components further hinders the transmission of lithium ions in the battery, which is not conducive to the performance of the battery's electrical performance. For example, patent FR3011682B1 proposes a phosphorus-containing polymer as an electrode adhesive, but the polymer needs to be stable at a higher temperature (~200°C) when used in fuel cells. If used in the field of lithium batteries, the polymer has a poor inhibitory effect on the early stage of thermal runaway of lithium batteries, and due to the lack of a design that promotes lithium ion conduction, the use of this compound is not conducive to the performance of lithium battery electrical performance.

[0004] In view of the deficiencies in the above-mentioned prior art, there is a need for a positive electrode that is suitable for liquid batteries and solid-state batteries, has good thermal stability and can effectively reduce the exothermic reaction in the early stage of thermal runaway, so as to improve the thermal safety of the battery. Summary of the invention

[0005] In view of the above-mentioned problems, the present invention proposes a high-safety polymer-modified positive electrode plate and a lithium battery, which overcome the shortcomings and defects mentioned in the background technology.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] One of the inventive aspects of the present invention is to provide a phosphonate polymerizable monomer.

[0008] Furthermore, the phosphate polymerizable monomer includes an unsaturated phosphate polymerizable monomer. The unsaturated phosphonate polymerizable monomer includes a phosphorus atom and two or more unsaturated carbon-carbon bonds, and at least one unsaturated carbon-carbon bond is directly connected to the phosphorus atom.

[0009] Optionally, the unsaturated carbon-carbon bond includes an unsaturated carbon-carbon double bond and an unsaturated carbon-carbon triple bond.

[0010] Optionally, the unsaturated carbon-carbon bond further includes a substituent; the substituent is a halogen.

[0011] Furthermore, the unsaturated phosphonate polymerizable monomer is vinyl phosphonate. The vinyl phosphonate comprises a phosphorus atom, a phosphorus oxygen bond and two or more unsaturated carbon-carbon bonds, wherein one unsaturated carbon-carbon bond is a vinyl group, which is directly connected to the phosphorus atom, and a substituent such as H, methyl, ethyl, halogen atom, etc. can be connected to the vinyl group.

[0012] Furthermore, the structure of the unsaturated phosphonate polymerizable monomer is as shown in Formula I:

[0013]

[0014] Wherein, R1 and / or R2 contain at least one unsaturated carbon-carbon bond, which can cause the unsaturated phosphonate polymerizable monomer to undergo polymerization reaction.

[0015] Preferably, in Formula I, the sum of the number of unsaturated carbon-carbon bonds located at R1 or R2 is 1.

[0016] That is, when there is only one unsaturated carbon-carbon bond in R1 or R2 that can undergo polymerization reaction. Unsaturated carbon-carbon bonds are the crosslinking points of polymers. When there is only one unsaturated carbon-carbon bond, a crosslinking structure can be formed, and the 3D crosslinking network formed by it has the best effect. For example, the uniformity and integrity of the 3D crosslinking network are better, which is manifested in the most obvious improvement in the electrical performance and safety performance of the battery. When neither R1 nor R2 contains unsaturated carbon-carbon bonds, it is difficult to form a crosslinking structure; in R1 and / or R2, if the number of unsaturated carbon-carbon bonds is more than 1, the crosslinking reaction activity is strong and the reaction speed is fast, which increases the difficulty of obtaining a uniform and complete crosslinking network.

[0017] Preferably, at least one unsaturated carbon-carbon bond is at a terminal end of R1 and / or R2.

[0018] When the unsaturated carbon-carbon bonds are at the end groups, a 3D cross-linked network is most easily formed, which results in the most obvious improvement in the battery's electrical and safety performance.

[0019] Preferably, R1 and / or R2 further contain non-carbon-carbon unsaturated bonds.

[0020] Preferably, the non-carbon-carbon unsaturated bond is a polar functional group.

[0021] The steric hindrance at the cross-linking point is large, which easily causes difficulties in lithium ion conduction. Introducing polar groups near the cross-linking point helps lithium ion conduction.

[0022] Preferably, the polar functional group includes at least one of an amide group, a ketone group, and an ester group.

[0023] Amide, ketone and ester groups are chemically stable and compatible with electrode and electrolyte systems; amide, ketone and ester groups are polar and facilitate lithium ion conduction.

[0024] Preferably, at least one carbon atom C at both ends of the unsaturated carbon-carbon bond is connected to at least one atom X at both ends of the non-carbon-carbon unsaturated bond; the connection mode is CX or CYX; Y is any one of O, S, CR3R4, NR5, PR6, PR7R8R9, wherein R3, R4, R5, R6, R7, R8, and R9 are independently selected from any one of hydrogen, halogen, alkyl, and halogenated alkyl.

[0025] The steric hindrance at the cross-linking point is large, which easily causes difficulty in lithium ion conduction and enhances battery polarization; the polar group interacts with the lithium ion, promoting the distribution and conduction of the lithium ion near the polar group. When the polar group is close to the cross-linking point, the conduction of the lithium ion near the cross-linking point can be accelerated; when the polar group is far away from the cross-linking point, the effect of the polar group on the distribution and conduction of the lithium ion near the cross-linking point is weakened; when the action range of the polar group is about 1 atomic radius, that is, the distance between at least one atom X at the two ends of the unsaturated carbon-carbon bond and the non-carbon-carbon unsaturated bond is not greater than one atom, at this time, not only is the steric hindrance small, but the polar group also has a strong effect of inducing lithium ion distribution and conduction, so that the generated cross-linked network has good lithium ion conductivity.

[0026] For example, an unsaturated carbon-carbon bond is C1=C2 or C1≡C2; a non-carbon-carbon unsaturated bond is M=N or M≡N.

[0027] Wherein, CX is: the unsaturated carbon-carbon bond can be linearly connected to the non-carbon-carbon unsaturated bond through C1-M, C2-M, C1-N or C2-N, or cyclically connected to the non-carbon-carbon unsaturated bond through C1-M, C2-N, or cyclically connected to the non-carbon-carbon unsaturated bond through C2-M, C1-N.

[0028] Wherein, CYX is: the unsaturated carbon-carbon bond can be linearly connected to the non-carbon-carbon unsaturated bond through C1-YM, C2-YM, C1-YN or C2-YN, or cyclically connected to the non-carbon-carbon unsaturated bond through C1-YM, C2-N, cyclically connected to the non-carbon-carbon unsaturated bond through C1-M, C2-YN, cyclically connected to the non-carbon-carbon unsaturated bond through C1-YM, C2-YN, or cyclically connected to the non-carbon-carbon unsaturated bond through C2-YM, C1-N, cyclically connected to the non-carbon-carbon unsaturated bond through C2-M, C1-YN, or cyclically connected to the non-carbon-carbon unsaturated bond through C2-YM, C1-YN.

[0029] Preferably, at least one unsaturated carbon-carbon bond in R1 and / or R2 further includes a halogen substituent; and the unsaturated carbon-carbon bond is on the terminal group.

[0030] Preferably, the halogen includes one or more of F, Cl, Br, and I.

[0031] Halogens can generate halogen free radicals when the battery is in thermal runaway, which can play a flame retardant role, thereby avoiding the occurrence of thermal runaway and greatly reducing the degree of thermal runaway when it occurs. At the same time, halogen substitution on unsaturated carbon-carbon bonds can reduce the electron cloud density of carbon-carbon unsaturated bonds, weaken carbon-carbon unsaturated bonds, help carbon-carbon unsaturated bonds to undergo free radical polymerization and promote the formation of cross-linked networks. This structure also helps halogen free radicals to be released when the battery is in thermal runaway.

[0032] Optionally, R1 and / or R2 are selected from at least one of hydrogen, alkanes, alkenes or alkynes with or without halogen substituents, ketone groups, ester groups, amides and isocyanates.

[0033] Preferably, the structure of R1 and / or R2 includes -H, -CH=CH2, -CH2F, -COCH3, -CONH2, -NHCOCH2CH=CH2, -NHCOCH=CH2, -NHCOCH2CH2CH=CH2, -NHCOCH2CBr=CH2, -NHCOCH(Br)CH=CH2, -COCH=CHF, -COCH=CH2, -CH=CHCH(Cl)CHCl2, -CH=CHCH2CH3, -CONHCH2CH2OOCC(CH3)=CH2, -CONHCH2CH2OOCC(CH3)=CHF, -CONHCF=CHOOCCHCH3CH3.

[0034] Preferably, the unsaturated phosphonate polymerizable monomer is selected from

[0035] At least one of .

[0036] The second inventive point of the present invention is to provide a polymer modified positive electrode plate.

[0037] The polymer modified positive electrode plate includes a cross-linked phosphonate polymer, a positive electrode active material, a positive electrode adhesive and a conductive additive. The cross-linked phosphonate polymer forms a 3D cross-linked network on the surface of the positive electrode plate and / or in the gaps between the positive electrode active materials; the cross-linked phosphonate polymer is prepared by coating an unsaturated phosphonate polymerizable monomer on the surface of the positive electrode plate, or mixing an unsaturated phosphonate polymerizable monomer into the positive electrode plate slurry and making the plate, and then completing in-situ polymerization and cross-linking during the plate baking process; the unsaturated phosphonate polymerizable monomer is the phosphonate polymerizable monomer or the unsaturated phosphonate polymerizable monomer described in any of the above paragraphs, and will not be repeated here.

[0038] In the unsaturated phosphonate polymerizable monomer, two or more unsaturated carbon-carbon bonds can enable the monomer to polymerize rapidly, and the vinyl group is directly connected to the phosphorus atom to generate phosphorus-containing free radicals, which are combined with the oxygen-containing free radicals generated during thermal runaway, thereby improving the thermal stability of the positive electrode; the amide group, ketone group, and ester group are polar and can accelerate lithium ion conduction, which helps to further improve the electrochemical performance of the positive electrode and the lithium battery; the halogen atom helps to further enhance the flame retardant effect.

[0039] Furthermore, the cross-linked phosphonate polymer is formed by in-situ polymerization and cross-linking of at least one unsaturated phosphonate polymerizable monomer described in Formula I, such as polymerization of only one unsaturated phosphonate polymerizable monomer, or polymerization of two or three monomers of Formula I; it can also be formed by in-situ polymerization and cross-linking of at least one unsaturated phosphonate polymerizable monomer described in Formula I with other unsaturated phosphonate monomers, where the other unsaturated phosphonate monomers refer to phosphonate monomers not within the scope of Formula I.

[0040] Preferably, the other unsaturated phosphate monomers may be: double-ended 2-methacryloyloxypoly(propylene glycol methyl phosphonate), double-ended 2-methacryloyloxypoly(diethylene glycol methyl phosphonate), single-ended 2-methacryloyloxypoly(propylene glycol methyl phosphonate), single-ended 2-methacryloyloxypoly(diethylene glycol methyl phosphonate), double-ended 2-methacryloyloxypoly(triethylene glycol methyl phosphonate), double-ended 2-methacryloyloxypoly(tetracetylene glycol methyl phosphonate), single-ended 2-methacryloyloxypoly(tetracetylene glycol methyl phosphonate). Among them, the double-ended 2-methacryloyloxypoly(propylene glycol methyl phosphonate) and single-ended 2-methacryloyloxypoly(propylene glycol methyl phosphonate) have the following structures:

[0041]

[0042] The "two ends" in this article refers to the presence of two 2-methacryloyloxy groups located at the end groups of the polymer, wherein one 2-methacryloyloxy group exists at the end group on one side; for example, in the double-terminal 2-methacryloyloxy poly(propylene glycol methyl phosphonate) shown in the figure above, the two 2-methacryloyloxy groups are respectively located at the two end groups of the poly(propylene glycol methyl phosphonate).

[0043] "Single-ended" herein means that there are two 2-methacryloyloxy groups located at the end groups of the polymer; for example, the single-ended 2-methacryloyloxy poly(propylene glycol methyl phosphonate) mentioned above has only one 2-methacryloyloxy group located at the end group on one side of the poly(propylene glycol methyl phosphonate).

[0044] Furthermore, in the polymer-modified positive electrode plate, the mass percentage of the cross-linked phosphonate polymer is 0.01 to 10%, preferably 0.01 to 3%.

[0045] Furthermore, the ratio of the cross-linked phosphonate polymer, the positive electrode active material, the positive electrode binder, and the conductive additive in the modified positive electrode is (0.01-10):(80-99):(0.1-10):(0.1-10).

[0046] Furthermore, the cross-linked phosphonate polymer is formed on the positive electrode plate by thermally initiated in-situ polymerization.

[0047] Furthermore, the positive electrode active material is one of lithium cobalt oxide, lithium nickel cobalt manganese oxide (NCM), lithium nickel cobalt aluminum oxide (NCA), lithium nickel manganese oxide, and lithium-rich material.

[0048] Furthermore, the conductive additive includes at least one of Super-P, KS-6, carbon black, nano-carbon fiber, carbon nanotube, acetylene black or graphene.

[0049] The positive electrode binder includes PVDF and / or PVDF-HFP.

[0050] Furthermore, the cross-linked phosphonate polymer forms a 3D cross-linked network on the surface of the positive electrode plate or in the gaps between the positive electrode active materials, and can generate phosphorus-containing free radicals to capture oxygen-containing free radicals below 200°C. This temperature is lower than the combustion temperature of the electrolyte, thereby effectively improving the thermal stability of the positive electrode and reducing the oxygen precipitation of the positive electrode, further blocking the reaction between the positive electrode and the electrolyte, reducing the heat release of the positive electrode, and improving the thermal safety of the battery.

[0051] The third inventive point of the present invention is to provide a method for preparing the polymer-modified positive electrode plate, the method comprising the following steps:

[0052] S1: adding an unsaturated phosphonate polymerizable monomer and an initiator to a positive electrode plate by blending or coating for modification, wherein the positive electrode plate comprises a positive electrode active material, a positive electrode binder and a conductive additive.

[0053] S2: Bake the positive electrode plate mixed or coated with unsaturated phosphonate polymerizable monomer and initiator, and make the unsaturated phosphonate polymerizable monomer undergo in-situ cross-linking polymerization by thermal initiation, the baking temperature is 30-80°C, and the baking time is 1-24 hours, so that the unsaturated phosphonate polymerizable monomer is fully polymerized to obtain a cross-linked phosphonate polymer, and a 3D cross-linked network is formed on the surface of the positive electrode plate or in the gap of the positive active material.

[0054] Furthermore, the unsaturated phosphonate polymerizable monomer is polymerized in situ during the positive electrode baking process, and the formed 3D cross-linked network is evenly distributed and independent of the bonding system of the positive electrode plate, which can simultaneously improve the bonding and safety of the positive electrode.

[0055] Furthermore, the unsaturated phosphonate polymerizable monomer includes vinyl phosphonate, and may also include other unsaturated phosphonates.

[0056] Furthermore, the initiator in S2 includes azobisisobutyronitrile, benzoyl peroxide, potassium persulfate, and ammonium persulfate, and the added amount of the initiator is 0.1% to 5% of the mass of the unsaturated phosphonate polymerizable monomer, preferably 0.5 to 1.5%.

[0057] Furthermore, the ratio of the cross-linked phosphonate polymer, the positive electrode active material, the positive electrode binder, and the conductive additive in the positive electrode is (0.01-10):(80-99):(0.1-10):(0.1-10).

[0058] The fourth inventive point of the present invention is to provide a secondary lithium battery including the polymer modified positive electrode plate.

[0059] The secondary lithium battery comprises the polymer-modified positive electrode sheet, negative electrode sheet and electrolyte described in any one of the above paragraphs, and the electrolyte comprises a liquid electrolyte, a solid electrolyte or a gel electrolyte.

[0060] Furthermore, the negative electrode active material is one of graphite, hard carbon, silicon, molybdenum disulfide, lithium titanate, graphene, silicon carbon, and silicon oxide negative electrode.

[0061] The present invention can be applied to liquid batteries and solid-state batteries, including liquid lithium-ion batteries, liquid metal lithium batteries, solid-state lithium-ion batteries, solid-state metal lithium batteries, and gel batteries.

[0062] Compared with the prior art, the present invention has the following advantages:

[0063] 1. The polymer-modified positive electrode plate provided by the present invention uses a specific monomer for polymerization. In the monomer structure, two or more unsaturated carbon-carbon bonds can make the monomer polymerize quickly. The vinyl group is directly connected to the phosphorus atom, which can generate phosphorus-containing free radicals at a lower temperature before thermal runaway occurs, and combine with the oxygen-containing free radicals generated during thermal runaway, thereby improving the thermal stability of the positive electrode; if it contains other unsaturated bonds such as amide, ketone, ester, etc. with suitable polarity and has suitable structural characteristics in the cross-linked network, it can also accelerate lithium ion conduction and further improve the electrochemical performance; halogen atoms are substituted on the unsaturated carbon-carbon bonds, which helps the formation of the cross-linked network, helps the release of halogen free radicals during thermal runaway, and plays a flame retardant role. The number of carbon-carbon unsaturated bonds is 2 (one is the vinyl group directly connected to the phosphorus element, and the other is that R1 and R2 have a total of only one unsaturated carbon-carbon bond) and when the end groups are distributed, the 3D cross-linked network formation effect is best, and the battery electrical performance and safety performance are optimal.

[0064] 2. The polymer-modified positive electrode and lithium battery provided by the present invention have good safety. The 3D cross-linked network can be uniformly formed on the surface of the positive electrode or in the gap between the positive electrode active materials at a relatively small amount of monomer addition, and more phosphorus-containing free radicals can be generated in situ at a relatively low temperature to capture oxygen-containing free radicals, thereby improving the thermal stability of the positive electrode and reducing the oxygen precipitation of the positive electrode, blocking the exothermic reaction between the positive electrode and the electrolyte, and improving the thermal safety of the battery.

[0065] 3. The polymer-modified positive electrode plate provided by the present invention can be used in combination with electrolyte / solid electrolyte without reducing the ion conductivity in the battery, so that the battery can give full play to its excellent electrochemical properties and can be applied to liquid batteries and solid-state batteries.

[0066] 4. Unlike the use of flame retardant adhesives that affect adhesion or flame retardancy, the 3D cross-linked network can simultaneously promote the adhesion and thermal safety of the positive electrode sheet. Since the positive electrode sheet is modified by a phosphonate polymer with a specific structure, the phosphonate polymer is compatible with the CEI membrane and the positive electrode bonding system, forming a 3D cross-linked network in the gap between the positive electrode active materials to enhance the adhesion of the positive electrode sheet. Therefore, the electrical performance of the modified positive electrode is relatively stable. BRIEF DESCRIPTION OF THE DRAWINGS

[0067] Figure 1 The cross-sectional schematic diagram of the electrode structure of the cross-linked phosphonate polymer added in the experimental group 1 includes the following main elements: a current collector 1, a positive electrode active material 2, and a cross-linked phosphonate polymer 3;

[0068] Figure 2 It is a schematic cross-sectional diagram of the electrode structure of the cross-linked phosphonate polymer added in the experimental group 11, which includes the following main elements: a current collector 1, a positive electrode active material 2, a cross-linked phosphonate polymer 3, and a cross-linked phosphonate polymer coating 4;

[0069] Figure 3 The infrared spectra of vinyl phosphoric acid, isocyanoethyl methacrylate and monomer C in Preparation Example 1; the abscissa is the wavelength, in cm -1 ; The vertical axis is transmittance, the unit is %;

[0070] Figure 4 The infrared spectra of vinyl phosphoric acid, isocyanoethyl methacrylate and monomer D in Preparation Example 2; the abscissa is the wavelength, in cm -1 ; The vertical axis is transmittance, the unit is %. DETAILED DESCRIPTION

[0071] In order to make the purpose, technical solution and advantages of the present invention more clear, the present invention is further described in detail below. However, it should be understood that the description herein is only used to explain the present invention and is not used to limit the scope of the present invention.

[0072] Unless otherwise defined, all technical terms and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention, and the terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The reagents and instruments used herein are all commercially available, and the characterization means involved can refer to the relevant descriptions in the prior art, which will not be repeated herein.

[0073] In order to further understand the present invention, the present invention is further described in detail below in conjunction with the best embodiment.

[0074] Preparation Example 1

[0075] A vinyl phosphonate monomer C in experimental group 5 was prepared, the structure of which is as described in formula I, wherein R1 and R2 are -H and -CONHCH2CH2OOCC(CH3)=CH2, respectively. Under an argon atmosphere, 3.307 parts by mass of vinyl phosphoric acid and 4.75 parts by mass of isocyanoethyl methacrylate were added to 10 parts by mass of dichloromethane, and 0.05 parts by mass of stannous octoate were added dropwise; the reaction was continued for 16 hours under an argon atmosphere at about 10°C. The dichloromethane was removed by rotary evaporation to obtain monomer C.

[0076] Monomer C can be initiated by 0.01 mass parts of azobisisobutyronitrile to form a polymerized product. The reaction can be scaled up as needed.

[0077] Comparison of infrared spectra of reactants before reaction (vinyl phosphate VPA and isocyanoethyl methacrylate IEMA) and products after reaction (monomer C) Figure 3 , -NCO in isocyanoethyl methacrylate is at 2400cm -1 The characteristic peaks disappeared after the reaction, proving that the reaction was complete.

[0078] Preparation Example 2

[0079] A vinyl phosphonate monomer D in experimental group 8 was prepared, the structure of which is as described in formula I, wherein R1 and R2 are both -CONHCH2CH2OOCC(CH3)=CH2. Under an argon atmosphere, 3.307 parts by mass of vinyl phosphoric acid and 9.5 parts by mass of isocyanoethyl methacrylate were added to 15 parts by mass of dichloromethane, and 0.05 parts by mass of stannous octoate were added dropwise; the reaction was continued for 16 hours under an argon atmosphere at about 10°C. The dichloromethane was removed by rotary evaporation to obtain monomer D.

[0080] Monomer D can be initiated by 0.01 mass parts of azobisisobutyronitrile to form a polymerized product. The reaction can be scaled up as needed.

[0081] Comparison of infrared spectra of reactants before reaction (vinyl phosphate VPA and isocyanoethyl methacrylate IEMA) and products after reaction (monomer D) Figure 4 , -NCO in isocyanoethyl methacrylate is at 2400cm -1 The characteristic peaks disappeared after the reaction, proving that the reaction was complete.

[0082] Preparation Example 3

[0083] A vinyl phosphonate monomer A in experimental group 1 was prepared, the structure of which is as described in formula I, wherein R1 and R2 are -H and -CH=CH2, respectively. Under an argon atmosphere, 3 parts by mass of vinyl phosphoric acid and 4 parts by mass of vinyl alcohol were mixed, and 0.05 parts by mass of stannous octoate were added dropwise; the reaction was continued in vacuum for 12 hours. Monomer A was obtained after separation and purification.

[0084] Monomer A can be initiated by 0.01 mass parts of azobisisobutyronitrile to form a polymerized product. The reaction can be scaled up as needed.

[0085] Preparation Example 4

[0086] A vinyl phosphonate monomer B in experimental group 2 was prepared, the structure of which is as described in formula I, wherein R1 and R2 are -H and -NHCOCH=CH2, respectively. Under an argon atmosphere, 3.307 parts by mass of vinyl phosphoric acid and 2.11 parts by mass of vinyl isocyanate were added to 10 parts by mass of dichloromethane, and 0.05 parts by mass of stannous octoate were added dropwise; the reaction was continued for 16 hours under an argon atmosphere at about 10°C. The dichloromethane was removed by rotary evaporation to obtain monomer B.

[0087] Monomer B can be initiated by 0.01 mass parts of azobisisobutyronitrile to form a polymerized product. The reaction can be scaled up as needed.

[0088] Preparation Example 5

[0089] A vinyl phosphonate monomer B1 in experimental group 3 was prepared, the structure of which is as described in formula I, wherein R1 and R2 are -H and -NHCOCH2CH=CH2, respectively. Under an argon atmosphere, 3.307 parts by mass of vinyl phosphoric acid and 2.54 parts by mass of allyl isocyanate were added to 10 parts by mass of dichloromethane, and 0.05 parts by mass of stannous octoate were added dropwise; the reaction was continued for 16 hours under an argon atmosphere at about 10°C. The dichloromethane was removed by rotary evaporation to obtain monomer B1.

[0090] Monomer B1 can be initiated by 0.01 parts by weight of azobisisobutyronitrile to form a polymerized product. The reaction can be scaled up as needed.

[0091] Preparation Example 6

[0092] A vinyl phosphonate monomer B2 in experimental group 4 was prepared, the structure of which is as described in formula I, wherein R1 and R2 are -H and -NHCOCH2CH2CH=CH2, respectively. Under an argon atmosphere, 3.307 parts by mass of vinyl phosphoric acid and 2.97 parts by mass of butyl isocyanate were added to 10 parts by mass of dichloromethane, and 0.05 parts by mass of stannous octoate were added dropwise; the reaction was continued for 16 hours under an argon atmosphere at about 10°C. The dichloromethane was removed by rotary evaporation to obtain monomer B2.

[0093] Monomer B2 can form a polymerized product under the initiation of 0.01 mass parts of azobisisobutyronitrile. The reaction can be scaled up as needed.

[0094] Preparation Example 7

[0095] A vinyl phosphonate monomer C1 in experimental group 6 was prepared, the structure of which is as described in formula I, wherein R1 and R2 are -H and -CONHCH2CH2OOCC(CH3)=CHF, respectively. Under an argon atmosphere, 3.307 parts by mass of vinyl phosphoric acid and 4.75 parts by mass of isocyanoethyl methacrylate were added to 10 parts by mass of dichloromethane, and 0.05 parts by mass of stannous octoate were added dropwise; the reaction was continued for 16 hours under an argon atmosphere at about 10°C. Dichloromethane was removed by rotary evaporation to obtain monomer C. Monomer C was fluorinated with perchloric acid fluoride, and monomer C1 was obtained after separation and purification.

[0096] Monomer C1 can be initiated by 0.01 parts by weight of azobisisobutyronitrile to form a polymerized product. The reaction can be scaled up as needed.

[0097] Preparation Example 8

[0098] A vinyl phosphonate monomer C2 in experimental group 7 was prepared, the structure of which is as described in formula I, wherein R1 and R2 are -H and -CONHCF=CHOOCCHCH3CH3, respectively. Under an argon atmosphere, 3.307 parts by mass of vinyl phosphoric acid and 4.75 parts by mass of NCO-CH=CH-OOCCHCH3CH3 were added to 10 parts by mass of dichloromethane, and 0.05 parts by mass of stannous octoate were added dropwise; the reaction was continued for 16 hours under an argon atmosphere at about 10°C. Dichloromethane was removed by rotary evaporation to obtain monomer C. Monomer C was fluorinated with fluorine gas, and monomer C2 was obtained after separation and purification.

[0099] 1 part by mass of NCO-CH=CH-OOCCHCH3CH3 is obtained by the polycondensation reaction of 1 part by mass of vinyl isocyanate and 1 part by mass of isobutyric acid, followed by separation and purification.

[0100] Monomer C2 can form a polymerized product under the initiation of 0.01 mass parts of azobisisobutyronitrile. The reaction can be scaled up as needed.

[0101] Preparation Example 9

[0102] Experimental group 9 was prepared using a vinyl phosphonate monomer E, whose structure is as described in Formula I, wherein R1 and R2 are -NHCOCH2CBr=CH2 and -COCH3, respectively. After 1 part by mass of B1 was completely reacted with 0.5 parts by mass of N-bromophthalimide, it was then polycondensed with 0.33 parts by mass of acetic acid, and 0.05 parts by mass of stannous octoate was dropwise added. The reaction was continued in vacuum for 12 hours, and monomer E was obtained after separation and purification.

[0103] Monomer E can form a polymerized product under the initiation of 0.01 mass parts of azobisisobutyronitrile. The reaction can be scaled up as needed.

[0104] Preparation Example 10

[0105] Experimental group 10 was prepared with a vinyl phosphonate monomer E1, whose structure is as described in formula I, wherein R1 and R2 are -NHCOCH(Br)CH=CH2 and -COCH3, respectively. 1 part by mass of B1 was reacted with 0.5 parts by mass of liquid bromine (containing a small amount of Cl2), and then polycondensed with 0.33 parts by mass of acetic acid, and 0.05 parts by mass of stannous octoate was dropwise added thereto. The reaction was continued in vacuum for 12 hours, and the monomer E1 was obtained after separation and purification.

[0106] Monomer E1 can form a polymerized product under the initiation of 0.01 mass parts of azobisisobutyronitrile. The reaction can be scaled up as needed.

[0107] Preparation Example 11

[0108] Preparation of experimental group 11 A vinyl phosphonate monomer F, the structure of which is as described in formula I, wherein R1 and R2 are -NHCOCH2CH=CH2 and -COCH=CHF, respectively. 1 part of monomer acrylic acid was fluorinated with 2 parts of perchloric acid fluoride; then polycondensed with 3 parts of B1, 0.05 parts of stannous octoate were added dropwise, and the reaction was continued in vacuum for 12 hours, and monomer F was obtained after separation and purification.

[0109] Monomer F can be initiated by 0.01 mass parts of azobisisobutyronitrile to form a polymerized product. The reaction can be scaled up as needed.

[0110] Preparation Example 12

[0111] Experimental group 16 was prepared by condensing 3 parts of vinyl phosphoric acid and 2 parts of vinyl butanol, followed by chlorination (Cl2 treatment), and then condensing with 1 part of carbamic acid to obtain product G.

[0112] Monomer G can be initiated by 0.01 mass parts of azobisisobutyronitrile to form a polymerized product. The reaction can be scaled up as needed.

[0113] Preparation Example 13

[0114] Experimental group 17 was prepared by condensing 3 parts of vinyl phosphoric acid and 2 parts of vinyl butanol, and then condensing them with 1 part of carbamic acid to obtain product G1.

[0115] Monomer G1 can be initiated by 0.01 parts by weight of azobisisobutyronitrile to form a polymerized product. The reaction can be scaled up as needed.

[0116] Example 1

[0117] An unsaturated phosphate polymerizable monomer, wherein the unsaturated phosphonate polymerizable monomer includes vinyl phosphonate, wherein the vinyl phosphonate contains a phosphorus atom and two or more unsaturated carbon-carbon bonds, wherein one unsaturated bond is a vinyl group, and the vinyl group is directly connected to the phosphorus atom; the cross-linked phosphonate polymer forms a 3D cross-linked network on a positive electrode sheet or in the gaps between positive electrode active materials.

[0118] The vinyl phosphonate has the following structure:

[0119]

[0120] Wherein, R1 and / or R2 contain at least one unsaturated carbon-carbon bond. Preferably, R1 and / or R2 also contain one or more of an amide group, a ketone group, an ester group, and a halogen atom.

[0121] For example, the vinyl phosphonate may be:

[0122]

[0123]

[0124] Example 2

[0125] A polymer-modified positive electrode plate comprises a cross-linked phosphonate polymer, a positive electrode active material, a positive electrode binder and a conductive additive. The modified positive electrode plate is coated or mixed with an unsaturated phosphonate polymerizable monomer as described in Example 1; the cross-linked phosphonate polymer forms a 3D cross-linked network on the positive electrode plate or in the gaps of the positive electrode active material.

[0126] In the modified positive electrode plate, the mass percentage of the cross-linked phosphonate polymer is 0.01-10%, such as 0.01%, 0.02%, 0.03%, 0.05%, 0.08%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.8%, 1%, 2%, 3%, 4%, 5%, 6%, 8%, 10%, etc., preferably 0.01-3%.

[0127] The positive electrode active material is one of lithium cobalt oxide, lithium nickel cobalt manganese oxide (NCM), nickel cobalt aluminum oxide (NCA), lithium nickel manganese oxide, and lithium-rich.

[0128] The conductive additive includes at least one of Super-P, KS-6, carbon black, nano-carbon fiber, carbon nanotube, acetylene black or graphene.

[0129] The positive electrode adhesive includes PVDF and PVDF-HFP.

[0130] Example 3

[0131] On the basis of Example 2, the unsaturated phosphonate polymerizable monomer may further include other unsaturated phosphonates, that is, the cross-linked phosphonate polymer is formed by co-polymerization of vinyl phosphonate and other unsaturated phosphonates, and the other unsaturated phosphonates may be: double-ended 2-methacryloyloxypoly(propylene glycol methyl phosphonate), double-ended 2-methacryloyloxypoly(diethylene glycol methyl phosphonate), single-ended 2-methacryloyloxypoly(propylene glycol methyl phosphonate), single-ended 2-methacryloyloxypoly(diethylene glycol methyl phosphonate), double-ended 2-methacryloyloxypoly(triethylene glycol methyl phosphonate), double-ended 2-methacryloyloxypoly(tetracetyl glycol methyl phosphonate), single-ended 2-methacryloyloxypoly(tetracetyl glycol methyl phosphonate).

[0132] The unsaturated phosphonate polymerizable monomer may be a combination of vinyl phosphonate and other unsaturated phosphonates, for example:

[0133] X1, double-terminated 2-methacryloyloxypoly(propylene glycol methyl phosphonate), double-terminated 2-methacryloyloxypoly(diethylene glycol methyl phosphonate), mass ratio of (1:0.01-0.1:0.01-0.1), such as 1:0.01:0.01, 1:0.05:0.1, 1:0.1:0.01, etc.;

[0134] X2, single-ended 2-methacryloyloxypoly(propylene glycol methyl phosphonate), single-ended 2-methacryloyloxypoly(diethylene glycol methyl phosphonate), mass ratio (1:0.01-0.1:0.01-0.1), such as 1:0.05:0.08, 1:0.1:0.05, 1:0.01:0.1, etc.;

[0135] X3, double-terminated 2-methacryloyloxypoly(tetracetyl methylphosphonate), single-terminated 2-methacryloyloxypoly(trieracetyl methylphosphonate), mass ratio of (1:0.01-0.1:0.01-0.1), such as 1:0.05:0.1, 1:0.05:0.01, 1:0.03:0.06, etc.;

[0136] X4, single-terminal 2-methacryloyloxypoly(tetracetyl methylphosphonate), double-terminal 2-methacryloyloxypoly(trieracetyl methylphosphonate), mass ratio is (1:0.01~0.1:0.01~0.1), such as 1:0.1:0.1, 1:0.01:0.1, 1:0.08:0.05, etc.

[0137] When the cross-linked phosphonate polymer is formed by polymerizing the vinyl phosphonate and other unsaturated phosphonates, the total mass percentage of the cross-linked phosphonate polymer in the modified positive electrode plate is still 0.01-10%.

[0138] Example 4

[0139] A method for preparing a polymer-modified positive electrode sheet comprises the following steps:

[0140] S1: adding an unsaturated phosphonate polymerizable monomer and an initiator to a positive electrode plate by blending or coating for modification, wherein the positive electrode plate comprises a positive electrode active material, a positive electrode binder and a conductive additive.

[0141] S2: Bake the positive electrode sheet mixed or coated with unsaturated phosphonate polymerizable monomer and initiator, and make the unsaturated phosphonate polymerizable monomer undergo in-situ crosslinking polymerization by thermal initiation, the baking temperature is 30-80°C, such as 30°C, 50°C, 80°C, etc., preferably 50-70°C; the baking time is 1-24 hours, such as 1 hour, 8 hours, 15 hours, 24 hours, etc., preferably 10-15 hours, so that the unsaturated phosphonate polymerizable monomer is fully polymerized to obtain a cross-linked phosphonate polymer, and a 3D cross-linked network is uniformly formed in situ on the surface of the positive electrode sheet or in the gap between the active materials. The initiator includes azobisisobutyronitrile, benzoyl peroxide, potassium persulfate, and ammonium persulfate.

[0142] The cross-linked phosphonate polymer can be obtained by polymerizing vinyl phosphonate alone, or by polymerizing vinyl phosphonate and other unsaturated phosphonates together.

[0143] Example 5

[0144] A secondary lithium battery comprises a positive electrode, a negative electrode and an electrolyte. The positive electrode is a mixture of a positive electrode active material, a positive electrode binder and a conductive additive, and the negative electrode is a mixture of a negative electrode active material, a negative electrode binder and a conductive additive. The ratio of the cross-linked phosphonate polymer, the positive electrode active material, the positive electrode binder and the conductive additive in the positive electrode is (0.01-10): (80-99): (0.1-10): (0.1-10); the ratio of the negative electrode active material, the negative electrode binder and the conductive additive in the negative electrode is (80-99): (0.1-10): (0.1-10). The positive electrode active material is one of lithium cobalt oxide, lithium nickel cobalt manganese oxide (NCM), nickel cobalt aluminum oxide (NCA), lithium nickel manganese oxide and lithium-rich. The negative electrode active material is one of graphite, hard carbon, silicon, molybdenum disulfide, lithium titanate, graphene, silicon carbon and silicon oxide negative electrode. The conductive additive includes at least one of Super-P, KS-6, carbon black, nano-carbon fiber, carbon nanotube, acetylene black or graphene. The lithium battery also includes a current collector.

[0145] Experimental Group 1

[0146] A vinyl phosphonate monomer A, the structure of which is as described in Formula I, wherein R1 and R2 are -H and -CH=CH2 respectively. 3 g of the monomer A and 0.03 g of the initiator azobisisobutyronitrile are mixed with an active material of LiNi 0.5 Mn 1.5 O4, PVDF as the positive electrode binder, and Super-P as the conductive additive, wherein the mass ratio of active material, positive electrode binder, and conductive additive is 84:5:8, and then baked at a baking temperature of 50°C for 12 hours. Then, the positive electrode sheet is rolled to obtain the polymer modified positive electrode sheet (as shown in the structural cross-section diagram) Figure 1 As shown, 1 is a current collector, 2 is a positive electrode material, and 3 is a cross-linked phosphonate polymer). After modification, the mass percentage of the cross-linked phosphonate polymer in the modified positive electrode sheet is 3%.

[0147] The modified positive electrode sheet was assembled into a secondary lithium battery according to Example 5, and the negative electrode was graphite. After the steps of liquid injection, formation, and capacity separation, the lithium battery prepared above was subjected to electrochemical tests and safety performance tests. The specific electrochemical performance test results of the lithium battery prepared using the positive electrode sheet are shown in Table 1, and the safety performance test results are shown in Table 2. The schematic diagram of the cross-section of the electrode sheet is shown in Figure 1 The current collector includes a positive electrode active material and a phosphonate polymer. The cross-linked phosphonate polymer forms a 3D cross-linked network in the gaps between the positive electrode active materials.

[0148] The electrochemical performance test method of lithium batteries used in this application document is as follows:

[0149] 1. Cycle performance test

[0150] a) At 23℃±2℃, charge at a constant current of 1C until the charge termination voltage is reached, then switch to constant voltage charging until the charge current rate drops to 0.05C, stop charging, and let stand for 1h;

[0151] b) The battery is discharged at a constant current of 1C until the discharge termination voltage is reached, then the discharge is stopped and the discharge capacity is recorded. This completes one cycle.

[0152] c) Repeat steps a and b until the discharge capacity is less than 80% of the discharge capacity in the first week, and record the total number of cycles of the battery at this time.

[0153] 2. Ratio test

[0154] a) At 23℃±2℃, the battery is charged at 0.1C, 0.2C, 0.33C, 1C, 2C, 3C to the charge termination voltage, then discharged at the same rate to the discharge termination voltage, and the same rate is cycled 4 times;

[0155] b) Record the discharge capacity at different rates;

[0156] c) Calculate the ratio of 3C discharge capacity to 0.33C discharge capacity, recorded as 3C / 0.33C, or calculate the ratio of 2C discharge capacity to 0.33C discharge capacity, recorded as 2C / 0.33C, and evaluate the rate performance.

[0157] 3. High temperature cycle

[0158] a) Charge at 1C constant current at 45°C until the charge termination voltage is reached, then switch to constant voltage charging until the charge current rate drops to 0.05C and stop charging;

[0159] b) The battery is left at 45°C for 5 hours;

[0160] c) At a high temperature of 45°C, the battery is discharged at a constant current of 1C until the discharge termination voltage is reached, then the discharge is stopped and the discharge capacity is recorded. This completes one cycle.

[0161] d) Repeat steps a to c until the discharge capacity is less than 80% of the discharge capacity in the first cycle, and record the discharge capacity of the battery and the total number of cycles at this time.

[0162] The lithium battery safety performance test method used in this application document is as follows:

[0163] 1. Overcharge

[0164] a) At 23℃±2℃, charge at a constant current of 1C until the charge termination voltage is reached, then switch to constant voltage charging until the charge current rate drops to 0.05C, stop charging, and let stand for 1h;

[0165] b) Continuously charge at a constant current of 1C until the battery experiences thermal runaway, and record the battery voltage when thermal runaway begins.

[0166] 2. Hot box

[0167] a) At 23℃±2℃, charge at a constant current of 1C until the charge termination voltage is reached, then switch to constant voltage charging until the charge current rate drops to 0.05C, stop charging, and let stand for 1h;

[0168] b) Place the battery in a test chamber. The test chamber is heated at a rate of 5°C / min. When the temperature inside the chamber reaches 160°C±2°C, the temperature is kept constant for 1 hour.

[0169] The battery passes if it does not emit smoke, catch fire or explode, otherwise it fails.

[0170] 3. Fall

[0171] a) At 23℃±2℃, charge at a constant current of 1C until the charge termination voltage is reached, then switch to constant voltage charging until the charge current rate drops to 0.05C, stop charging, and let stand for 1h;

[0172] b) Drop freely from a drop height of 1m onto a concrete slab; each side of the soft-pack battery drops once, and a total of six tests are performed; after six tests, the battery passes if there is no smoke, fire, or explosion, otherwise it fails.

[0173] 4. Heavy object impact

[0174] a) At 23℃±2℃, charge at a constant current of 1C until the charge termination voltage is reached, then switch to constant voltage charging until the charge current rate drops to 0.05C, stop charging, and let stand for 1h;

[0175] b) Place the battery on the platform surface, and place a metal rod with a diameter of 15.8mm±0.2mm horizontally on the upper surface of the geometric center of the battery. Use a weight of 9.1kg±0.1kg to hit the battery surface with the metal rod in a free fall state from a height of 610mm±25mm, and observe for 6 hours. If the battery does not smoke, catch fire or explode, it passes, otherwise it fails.

[0176] 5. Acupuncture

[0177] a) Charge at 1C constant current at 23℃±2℃ until the charge termination voltage is reached, then switch to constant voltage charging until the charge current rate drops to 0.05C, stop charging, and let stand for 1h;

[0178] b) Use a φ8mm high temperature resistant steel needle (the cone angle of the needle tip is 45°, the needle surface is smooth, free of rust, oxide layer and oil stains) to penetrate the battery plate at a speed of 25mm / s from a direction perpendicular to the battery plate. The penetration position is the geometric center of the pierced surface, and the steel needle stays in the battery;

[0179] c) Observe for 1 hour; if the battery does not emit smoke, catch fire or explode, it passes; otherwise, it fails.

[0180] Experimental Group 2

[0181] A vinyl phosphonate monomer B, the structure of which is as described in Formula I, wherein R1 and R2 are -H and -NHCOCH=CH2, respectively. The rest is consistent with Experimental Group 1. The lithium battery prepared above is subjected to electrochemical tests and safety performance tests after steps such as liquid injection, formation, and volume separation. The specific electrochemical performance test results of the lithium battery prepared using the positive electrode sheet are shown in Table 1, and the safety performance test results are shown in Table 2.

[0182] Experimental Group 3

[0183] A vinyl phosphonate monomer B1, the structure of which is as described in Formula I, wherein R1 and R2 are -H and -NHCOCH2CH=CH2, respectively. The rest is consistent with Experimental Group 1. The lithium battery prepared above is subjected to electrochemical tests and safety performance tests after steps such as liquid injection, formation, and volume separation. The specific electrochemical performance test results of the lithium battery prepared using the positive electrode sheet are shown in Table 1, and the safety performance test results are shown in Table 2.

[0184] Experimental Group 4

[0185] A vinyl phosphonate monomer B2, the structure of which is as described in Formula I, wherein R1 and R2 are -H and -NHCOCH2CH2CH=CH2, respectively. The rest is consistent with Experimental Group 1. The lithium battery prepared above is subjected to electrochemical tests and safety performance tests after steps such as liquid injection, formation, and capacity separation. The specific electrochemical performance test results of the lithium battery prepared using the positive electrode sheet are shown in Table 1, and the safety performance test results are shown in Table 2.

[0186] Experimental Group 5

[0187] A vinyl phosphonate monomer C, the structure of which is as described in Formula I, wherein R1 and R2 are -H and -CONHCH2CH2OOCC(CH3)=CH2, respectively. The positive electrode is NCM90, the negative electrode is SiOC650, 2g of monomer C and 0.02g of initiator azobisisobutyronitrile are mixed together in the positive electrode plate, wherein the positive electrode plate includes active material NCM90, positive electrode binder PVDF, and conductive additive acetylene black, the mass ratio of the three is 94:1:3, and the mass percentage of cross-linked phosphonate polymer in the modified positive electrode plate after modification is 2%. Others are consistent with experimental group 1. After the steps of liquid injection, formation, and volume separation, the lithium battery prepared as above is subjected to electrochemical testing and safety performance testing respectively. The specific electrochemical performance test results of the lithium battery prepared using the positive electrode plate are shown in Table 3, and the safety performance test results are shown in Table 4.

[0188] Experimental Group 6

[0189] A vinyl phosphonate monomer C1, the structure of which is as described in Formula I, wherein R1 and R2 are -H and -CONHCH2CH2OOCC(CH3)=CHF, respectively, and the others are consistent with Experimental Group 5. The lithium battery prepared above was subjected to electrochemical tests and safety performance tests after steps such as liquid injection, formation, and volume separation. The specific electrochemical performance test results of the lithium battery prepared using the positive electrode sheet are shown in Table 3, and the safety performance test results are shown in Table 4.

[0190] Experimental Group 7

[0191] A vinyl phosphonate monomer C2, the structure of which is as described in Formula I, wherein R1 and R2 are -H and -CONHCF=CHOOCCHCH3CH3, respectively, and the others are consistent with Experimental Group 5. The lithium battery prepared above was subjected to electrochemical tests and safety performance tests after steps such as liquid injection, formation, and volume separation. The specific electrochemical performance test results of the lithium battery prepared using the positive electrode sheet are shown in Table 3, and the safety performance test results are shown in Table 4.

[0192] Experimental Group 8

[0193] A vinyl phosphonate monomer D, having a structure as described in Formula I, wherein R1 and R2 are both -CONHCH2CH2OOCC(CH3)=CH2. The step parameters are consistent with those of Experimental Group 5. After the steps of liquid injection, formation, and volume separation, the lithium battery prepared above was subjected to electrochemical tests and safety performance tests respectively. The specific electrochemical performance test results of the lithium battery prepared using the positive electrode sheet are shown in Table 3, and the safety performance test results are shown in Table 4.

[0194] Experimental Group 9

[0195] A vinyl phosphonate monomer E, the structure of which is as described in Formula I, wherein R1 and R2 are -NHCOCH2CBr=CH2 and -COCH3, respectively. 3g of monomer B and 0.045g of initiator azobisisobutyronitrile are mixed together with a positive electrode plate having NCM83 as an active material, PVDF as a positive electrode binder, and carbon black as a conductive additive, wherein the mass ratio of the active material, the positive electrode binder, and the conductive additive is 84:5:8, and then baked at a baking temperature of 70°C for 10 hours. The positive electrode plate is then rolled to obtain the polymer-modified positive electrode plate. After modification, the mass percentage of the cross-linked phosphonate polymer in the modified positive electrode plate is 3%. The modified positive electrode plate is assembled into a secondary lithium battery according to the method described in Example 5, and the negative electrode is SiOC450. After the steps of liquid injection, formation, and volume separation, the lithium battery prepared above is subjected to electrochemical testing and safety performance testing respectively. The specific electrochemical performance test results of the lithium battery prepared using the positive electrode sheet are shown in Table 5, and the safety performance test results are shown in Table 6.

[0196] Experimental Group 10

[0197] A vinyl phosphonate monomer E1, the structure of which is as described in Formula I, wherein R1 and R2 are -NHCOCH(Br)CH=CH2 and -COCH3, respectively. The rest are consistent with Experimental Group 9. The lithium battery prepared above was subjected to electrochemical tests and safety performance tests after steps such as liquid injection, formation, and volume separation. The specific electrochemical performance test results of the lithium battery prepared using the positive electrode sheet are shown in Table 5, and the safety performance test results are shown in Table 6.

[0198] Experimental Group 11

[0199] A vinyl phosphonate monomer F, the structure of which is as described in Formula I, wherein R1 and R2 are -NHCOCH2CH=CH2 and -COCH=CHF, respectively. 3g of monomer C and 0.045g of initiator azobisisobutyronitrile are co-coated on the surface of a positive electrode sheet whose active material is NCM83, whose positive electrode binder is PVDF-HFP, and whose conductive additive is carbon nanotubes, wherein the mass ratio of the active material, the positive electrode binder, and the conductive additive is 84:5:8, and then baked at a baking temperature of 70°C for 15 hours to form a coating. The positive electrode sheet is then rolled to obtain the polymer-modified positive electrode sheet (as shown in the structural cross-section diagram). Figure 2 As shown: 1 is a current collector, 2 is a positive electrode material, 3 is a cross-linked phosphonate polymer, and 4 is a cross-linked phosphonate polymer coating). After modification, the mass percentage of the cross-linked phosphonate polymer in the modified positive electrode sheet is 3%.

[0200] The modified positive electrode sheet was assembled into a secondary lithium battery according to Example 5, and the negative electrode was SiOC450. After the steps of liquid injection, formation, and capacity separation, the lithium battery prepared above was subjected to electrochemical tests and safety performance tests respectively. The specific electrochemical performance test results of the lithium battery prepared using the positive electrode sheet are shown in Table 5, and the safety performance test results are shown in Table 6. The schematic diagram of the cross-section structure of the electrode sheet is shown in Figure 2 As shown, the current collector includes positive electrode active materials and phosphonate polymers. The cross-linked phosphonate polymers are mainly distributed on the surface of the positive electrode plate, and can also penetrate into the plate to a certain depth and be distributed between the positive electrode active materials.

[0201] Experimental Group 12

[0202] A vinyl phosphonate monomer F, the structure of which is as described in Formula I, wherein R1 and R2 are -NHCOCH2CH=CH2 and -COCH=CHF, respectively. 0.01g of monomer C and 0.00015g of initiator azobisisobutyronitrile are co-coated on the surface of a positive electrode sheet having NCM83 as an active material, PVDF-HFP as a positive electrode binder, and carbon nanotubes as a conductive additive, wherein the mass ratio of the active material, the positive electrode binder, and the conductive additive is 95.99:2:2, and then baked at a baking temperature of 70°C for 15 hours to form a coating. The positive electrode sheet is then rolled to obtain the polymer-modified positive electrode sheet. After modification, the mass percentage of the cross-linked phosphonate polymer in the modified positive electrode sheet is 0.01%. The modified positive electrode sheet is assembled into a secondary lithium battery according to Example 5, and the negative electrode is SiOC450. After the steps of liquid injection, formation, and capacity separation, the lithium battery prepared above was subjected to electrochemical test and safety performance test. The specific electrochemical performance test results of the lithium battery prepared using the positive electrode sheet are shown in Table 5, and the safety performance test results are shown in Table 6.

[0203] Experimental Group 13

[0204] A vinyl phosphonate monomer F, the structure of which is as described in Formula I, wherein R1 and R2 are -NHCOCH2CH=CH2 and -COCH=CHF, respectively. 10g of monomer C and 0.15g of initiator azobisisobutyronitrile are co-coated on the surface of a positive electrode sheet whose active material is NCM83, whose positive electrode binder is PVDF-HFP, and whose conductive additive is carbon nanotube, wherein the mass ratio of the active material, the positive electrode binder, and the conductive additive is 88:1:1, and then baked at a baking temperature of 70°C for 15 hours to form a coating. The positive electrode sheet is then rolled to obtain the polymer-modified positive electrode sheet. After modification, the mass percentage of the cross-linked phosphonate polymer in the modified positive electrode sheet is 10%. The modified positive electrode sheet is assembled into a secondary lithium battery according to Example 5, and the negative electrode is SiOC450. After the steps of liquid injection, formation, and capacity separation, the lithium battery prepared above is subjected to electrochemical tests and safety performance tests respectively. The specific electrochemical performance test results of the lithium battery prepared using the positive electrode sheet are shown in Table 5, and the safety performance test results are shown in Table 6.

[0205] Experimental Group 14

[0206] The positive electrode is LCO, the negative electrode is SiOC450, the initiator concentration is adjusted to 0.5% of the mass of the polymer monomer, and the other parameters are consistent with those of experimental group 11, and monomer F is still used. After the steps of liquid injection, formation, and volume separation, the lithium battery prepared above was subjected to electrochemical tests and safety performance tests respectively. The specific electrochemical performance test results of the lithium battery prepared using the positive electrode sheet are shown in Table 7, and the safety performance test results are shown in Table 8.

[0207] Experimental Group 15

[0208] It is basically the same as experimental group 14, except that R2 does not contain halogen atoms, that is, the fluorine atom F is replaced by a hydrogen atom. After the steps of liquid injection, formation, and volume separation, the lithium battery prepared above was subjected to electrochemical tests and safety performance tests respectively. The specific electrochemical performance test results of the lithium battery prepared using the positive electrode sheet are shown in Table 7, and the safety performance test results are shown in Table 8.

[0209] Experimental Group 16

[0210] A vinyl phosphonate monomer G, the structure of which is as described in Formula I, wherein R1 and R2 are -CH=CH-CHClCHCl2 and -CONH2, respectively, and the other parameters are consistent with those of Experimental Group 14. The lithium battery prepared above was subjected to electrochemical tests and safety performance tests after steps such as liquid injection, formation, and volume separation. The specific electrochemical performance test results of the lithium battery prepared using the positive electrode sheet are shown in Table 7, and the safety performance test results are shown in Table 8.

[0211] Experimental Group 17

[0212] It is basically the same as experimental group 16, except that R1 does not contain halogen atoms, that is, the chlorine atom Cl is replaced by a hydrogen atom. After the steps of liquid injection, formation, and volume separation, the lithium battery prepared above was subjected to electrochemical tests and safety performance tests respectively. The specific electrochemical performance test results of the lithium battery prepared using the positive electrode sheet are shown in Table 7, and the safety performance test results are shown in Table 8.

[0213] Experimental Group 18

[0214] A vinyl phosphonate C, the structure of which is as described in Formula I, wherein R1 and R2 are -H and -CONHCH2CH2OOCC(CH3)=CH2. 2g of monomer C is mixed with 0.1g of double-terminal dimethacryloxypoly (tetracetylene glycol methylphosphonate), 0.1g of single-terminal dimethacryloxypoly (tetracetylene glycol methylphosphonate), 0.1g of single-terminal dimethacryloxypoly (tetracetylene glycol methylphosphonate) and 0.02g of initiator azobisisobutyronitrile and mixed together in a positive electrode plate, wherein the positive electrode plate includes active material NCM90, positive electrode binder PVDF, and conductive additive acetylene black, the mass ratio of the three is 94:1:3, and then baked, the baking temperature is 60°C, and the baking time is 10 hours. Then the positive electrode plate is rolled to obtain the polymer-modified positive electrode plate. After modification, the mass percentage of the cross-linked phosphonate polymer in the modified positive electrode plate is 2%. The modified positive electrode sheet was assembled into a secondary lithium battery according to Example 5, and the negative electrode was SiOC650. After the steps of liquid injection, formation, and capacity separation, the lithium battery prepared above was subjected to electrochemical tests and safety performance tests. The specific electrochemical performance test results of the lithium battery prepared using the positive electrode sheet are shown in Table 3, and the safety performance test results are shown in Table 4.

[0215] Experimental Group 19

[0216] It is basically the same as experimental group 5, except that the baking temperature is 80°C and the baking time is 20 hours. After the steps of liquid injection, formation, and capacity separation, the lithium battery prepared above was subjected to electrochemical testing and safety performance testing respectively. The specific electrochemical performance test results of the lithium battery prepared using the positive electrode sheet are shown in Table 3, and the safety performance test results are shown in Table 4.

[0217] Experimental Group 20

[0218] It is basically the same as experimental group 5, except that the baking temperature is 30°C and the baking time is 5 hours. After the steps of liquid injection, formation, and capacity separation, the lithium battery prepared above was subjected to electrochemical testing and safety performance testing respectively. The specific electrochemical performance test results of the lithium battery prepared using the positive electrode sheet are shown in Table 3, and the safety performance test results are shown in Table 4.

[0219] Experimental Group 21

[0220] The results are basically the same as those of Experimental Group 5, except that the initiator concentration is 0.1%. After the steps of liquid injection, formation, and volume separation, the lithium battery prepared above was subjected to electrochemical tests and safety performance tests. The specific electrochemical performance test results of the lithium battery prepared using the positive electrode sheet are shown in Table 3, and the safety performance test results are shown in Table 4.

[0221] Experimental Group 22

[0222] The results are basically the same as those of Experimental Group 5, except that the initiator concentration is 5%. After the steps of liquid injection, formation, and volume separation, the lithium battery prepared above was subjected to electrochemical tests and safety performance tests. The specific electrochemical performance test results of the lithium battery prepared using the positive electrode sheet are shown in Table 3, and the safety performance test results are shown in Table 4.

[0223] In all the above experimental groups, the total mass of the phosphonate monomer, active material, positive electrode binder, and conductive additive was 100 g.

[0224] Comparative Example 1

[0225] A secondary battery was assembled according to Example 5 using a normal positive electrode sheet, i.e., the positive electrode sheet did not contain a cross-linked phosphonate polymer, and no unsaturated phosphonate polymerizable monomer was added during the preparation of the positive electrode sheet. The positive electrode was NCM90 and the negative electrode was SiOC650. The lithium battery prepared above was subjected to electrochemical tests and safety performance tests after steps such as injection, formation, and capacity separation. The specific electrochemical performance test results of the lithium battery prepared using the positive electrode sheet are shown in Table 3, and the safety performance test results are shown in Table 4.

[0226] Comparative Example 2

[0227] It is basically the same as the experimental group 18, except that the monomer C is omitted, and 1 mass part of double-terminal dimethacryloxy poly (tetracetylene glycol methyl phosphonate), 1 mass part of single-terminal dimethacryloxy poly (tetracetylene glycol methyl phosphonate), 1 mass part of single-terminal dimethacryloxy poly (tetracetylene glycol methyl phosphonate) and 0.03 mass part of initiator azobisisobutyronitrile are mixed together in the positive electrode sheet, and the mass percentage of polyphosphonate in the modified electrode sheet is 2%. After the steps of liquid injection, formation, and volume separation, the lithium battery prepared above is subjected to electrochemical testing and safety performance testing respectively. The specific electrochemical performance test results of the lithium battery prepared using the positive electrode sheet are shown in Table 3, and the safety performance test results are shown in Table 4.

[0228] Comparative Example 3

[0229] The same as experimental group 2, except that the monomer B was changed to

[0230] After the steps of liquid injection, formation, and capacity separation, the lithium battery prepared above was subjected to electrochemical test and safety performance test. The specific electrochemical performance test results of the lithium battery prepared using the positive electrode sheet are shown in Table 1, and the safety performance test results are shown in Table 2.

[0231] Comparative Example 4

[0232] The same as experimental group 2, except that the monomer B was changed to

[0233] After the steps of liquid injection, formation, and capacity separation, the lithium battery prepared above was subjected to electrochemical test and safety performance test. The specific electrochemical performance test results of the lithium battery prepared using the positive electrode sheet are shown in Table 1, and the safety performance test results are shown in Table 2.

[0234] Comparative Example 5

[0235] The same as Experimental Group 14, except that the monomer is changed to a vinyl phosphonate monomer, the structure of which is as described in Formula I, wherein R1 and R2 are -NHCOCH2CH2CH3 and -COCH2CH2F, respectively.

[0236] After the steps of liquid injection, formation, and capacity separation, the prepared lithium battery was subjected to electrochemical tests and safety performance tests. The specific electrochemical performance test results of the lithium battery prepared using the positive electrode sheet are shown in Table 7, and the safety performance test results are shown in Table 8.

[0237] Comparative Example 6

[0238] The same as comparative example 5, except that the positive electrode is changed to NCM83, the negative electrode is SiOC450, and the initiator concentration is adjusted to 1.5% of the mass of the polymer monomer. The lithium battery prepared above is subjected to the steps of liquid injection, formation, and volume separation, and then electrochemical tests and safety performance tests are performed respectively. The specific electrochemical performance test results of the lithium battery prepared using the positive electrode sheet are shown in Table 5, and the safety performance test results are shown in Table 6.

[0239] The performance tests were performed on the secondary lithium batteries of the experimental groups 1 to 22 and the comparative examples 1 to 6.

[0240] The cross-linked phosphonate polymer modified lithium battery provided by the present invention performs well in hot box test, heavy object impact, drop test, needle puncture test and overcharge voltage test, while the lithium battery that is not modified by the cross-linked phosphonate polymer provided by the present invention is difficult to pass the above safety performance tests, indicating that the safety of lithium batteries can be greatly improved by cross-linked phosphonate polymer modification. Because battery safety is directly related to the battery system, the above comparison is based on the same type of battery. The use of this technology can improve the safety performance of the battery without significantly reducing or improving the electrical performance of the battery.

[0241] Table 1 shows the electrochemical performance test results of LNMO||Gr battery.

[0242]

[0243] Table 2 shows the safety performance test results of LNMO||Gr battery.

[0244] Hot box pass rate Heavy object impact passing rate Drop pass rate Acupuncture pass rate Overcharge voltage Experimental Group 1 4 / 5 5 / 5 5 / 5 4 / 5 7.2V Experimental Group 2 4 / 5 5 / 5 5 / 5 4 / 5 7.3V Experimental Group 3 4 / 5 5 / 5 5 / 5 4 / 5 7.3V Experimental Group 4 4 / 5 5 / 5 5 / 5 4 / 5 7.2V Comparative Example 3 2 / 5 1 / 5 3 / 5 2 / 5 5.8V Comparative Example 4 2 / 5 1 / 5 2 / 5 2 / 5 5.8V

[0245] As can be seen from Table 1, in the electrochemical performance test, the cross-linked phosphonate polymer-modified lithium battery positive electrode of the present application not only did not reduce the battery cycle performance, but also improved it to a certain extent. Compared with the experimental group 1, the monomer R2 of the experimental group 2 has an additional amide bond, which accelerates the lithium ion conduction and further improves the electrochemical performance. Therefore, in Table 1, the room temperature cycle number of the experimental group 2 is higher than that of the experimental group 1; there is a carbon atom in the amide bond and the unsaturated carbon-carbon bond in the experimental group 3, and the battery electrical performance is similar to that of the experimental group 2 and slightly lower than that of the experimental group 2; there is a distance of two carbon atoms in the amide bond and the unsaturated carbon-carbon bond in the experimental group 4, which weakens the effect of the amide bond on the distribution and conduction of lithium ions, so its electrical performance is less than that of the experimental group 2 and the experimental group 3.

[0246] As shown in Table 2, in the monomer of Comparative Example 3, the vinyl group is not directly connected to the phosphorus element, and it is difficult to generate phosphorus-containing free radicals, so the effect of preventing thermal runaway is weakened; in the monomer of Comparative Example 4, R1 and R2 do not contain unsaturated carbon-carbon bonds, and a cross-linked structure cannot be generated during polymerization, which makes it difficult to promote the further release of phosphorus-containing free radicals, and the phosphorus-containing free radicals cannot fully contact the active positive electrode to play a role in inhibiting thermal runaway; therefore, the safety performance of Comparative Examples 3 and 4 is much lower than that of Experimental Group 2. The cross-linked phosphonate polymer-modified lithium battery positive electrodes of Experimental Groups 1 to 4 have excellent results in hot box tests, heavy object impact, drop tests, needle puncture tests, and overcharge voltage tests, and the overcharge voltage is much higher than that of Comparative Examples 3 and 4, and can withstand higher charging voltages.

[0247] Table 3 shows the electrochemical performance test results of NCM90||SiOC650 battery.

[0248]

[0249] Table 4 shows the safety performance test results of NCM90||SiOC650 battery.

[0250]

[0251]

[0252] It can be seen from Table 3 that, compared with Comparative Examples 1 and 2, the addition of the cross-linked phosphonate polymer in the experimental group of the present application not only does not reduce the electrochemical performance of the battery, but also has a certain improvement effect.

[0253] As shown in Table 4, there is only one unsaturated carbon-carbon bond in R1 and R2 of experimental group 5, while there are two unsaturated carbon-carbon bonds in R1 and R2 of experimental group 8; the safety performance of experimental group 5 is higher than that of experimental group 8, which can explain that when the number of unsaturated carbon-carbon bonds in R1 and R2 is more than one, the cross-linking reaction will be excessive, forming a complex cross-linked network structure, and the overly complex network structure with high cross-linking is not conducive to the release of phosphorus-containing free radicals. Therefore, compared with the cross-linked phosphonate polymer network structure with only one unsaturated carbon-carbon bond polymerization in experimental group 5, the safety performance of experimental group 8 is slightly reduced. There are halogen atoms on the terminal carbon-carbon double bond in the structure of formula I of experimental group 6, which can play a flame retardant role through the released halogen free radicals and reduce the degree of thermal runaway. Therefore, compared with the case where experimental group 5 does not contain halogen, the safety performance of experimental group 6 is better. Experimental Group 7 In the structure of Formula I, there is a halogen atom on the carbon-carbon double bond, but the carbon-carbon double bond is not at the end group. Its effect of improving the battery's electrical performance and safety performance is weaker than that of Experimental Group 6, but better than that of Experimental Group 5.

[0254] The main difference between Experimental Group 18 and Experimental Group 5 is that the phosphonate polymer used in Experimental Group 18 is formed by in-situ polymerization and crosslinking of the unsaturated phosphonate polymerizable monomer of Formula I and other unsaturated phosphonate monomers, while Experimental Group 5 is formed by polymerizing the unsaturated phosphonate polymerizable monomer of Formula I alone. It can be seen in Table 4 that the electrical performance of Experimental Group 18 is slightly lower than that of Experimental Group 5, and its safety performance is also slightly lower, but it is still better than Comparative Example 1.

[0255] In experimental group 19, the polymerization temperature was 80℃ and the time was 20h. The monomers would be over-polymerized under high temperature for a long time, making the network structure too tight, which was not conducive to the release of phosphorus-containing free radicals and also reduced the conductivity of lithium ions. In experimental group 20, due to insufficient temperature and time, the polymerization degree was too low, forming a relatively sparse network structure, which could not effectively improve the electrochemical performance of the battery and significantly enhance the safety performance. The temperature range of 50-70℃ and the time of 10-15h are more suitable conditions. The influence of the polymer prepared within this range on the electrochemical performance and safety performance of the battery can be ignored.

[0256] The difference between Experimental Group 21 and Experimental Group 22 and Experimental Group 5 lies in the concentration of the initiator. When the initiator content is too high (>5%) or too low (<0.1%), it will affect the network structure, thereby reducing certain electrical and safety performances compared to Experimental Group 5.

[0257] From the above, it can be seen that when the initiator concentration is within the range of 0.5-1.5%, the baking temperature is 50-70°C, and the baking time is 10-15 hours, the battery will not be affected by the changes in the above factors in terms of electrochemical performance and safety performance. The preferred experiments of this application are all conducted within the above preferred range based on the above experimental test results.

[0258] Table 5 shows the electrochemical performance test results of NCM83||SiOC450 battery.

[0259]

[0260]

[0261] Table 6 shows the safety performance test results of NCM83||SiOC450 battery.

[0262] Hot box pass rate Heavy object impact passing rate Drop pass rate Acupuncture pass rate Overcharge voltage Experimental Group 9 4 / 5 4 / 5 5 / 5 4 / 5 5.9V Experimental Group 10 3 / 5 4 / 5 5 / 5 3 / 5 5.6V Experimental Group 11 4 / 5 5 / 5 5 / 5 4 / 5 5.9V Experimental Group 12 4 / 5 5 / 5 5 / 5 4 / 5 5.9V Experimental Group 13 4 / 5 5 / 5 5 / 5 4 / 5 5.9V Comparative Example 6 1 / 5 0 / 5 0 / 5 1 / 5 4.7V

[0263] It can be seen from Tables 5 and 6 that when the halogen is directly substituted on the carbon-carbon double bond at the end group, the electrical properties and safety performance are most significantly improved, which is better than the case where the halogen is not substituted on the carbon-carbon double bond.

[0264] Comparing Experimental Group 11 and Comparative Example 6, it can be seen that when the polymer contains halogen but cannot form a sufficient cross-linking structure, that is, when there is no unsaturated carbon-carbon bond on R1 and / or R2, the safety performance is worse than when a cross-linking structure can be formed.

[0265] Table 7 shows the electrochemical performance test results of LCO||SiOC450 battery.

[0266]

[0267] Table 8 shows the safety performance test results of LCO||SiOC450 battery.

[0268]

[0269]

[0270] As shown in Tables 7 and 8, within the preferred range of the effective concentration of the initiator (i.e., when there is no significant effect on the electrochemical performance and safety performance of the battery), the difference between Experimental Group 14 and Experimental Group 15 is that there is a halogen F substitution in the unsaturated carbon-carbon bond of Experimental Group 14, and the halogen free radicals released can play a flame retardant role and reduce the degree of thermal runaway. Therefore, the safety performance of Experimental Group 14 is better than that of Experimental Group 15. Similarly, the safety performance of Experimental Group 16 is better than that of Experimental Group 17 due to the presence of multiple halogen substitutions on the hydrogen on the terminal groups. However, there is no unsaturated carbon-carbon bond in R1 and R2 of the monomer of Comparative Example 5. Even if it contains halogen, it still cannot form a cross-linked structure and cannot improve the safety and electrical performance of the battery. Therefore, its electrical performance and safety performance are inferior to those of Experimental Group 14.

[0271] In the present invention, the experimental conditions such as the negative electrode and the electrolyte are not the inventive point of the present invention, and their influence on the inventive point is also very small. Therefore, the embodiment part is only briefly mentioned, and the specific conventional method of the prior art can be used. During the experiment, as long as the experimental conditions not mentioned in the experimental group are ensured to be consistent in each experimental group and the comparison group, nothing else matters.

[0272] Finally, it should be noted that the above-described embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some or all of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A polymer-modified positive electrode sheet, comprising a cross-linked phosphonate polymer, a positive electrode active material, a positive electrode binder and a conductive additive, characterized in that: The cross-linked phosphonate polymer forms a 3D cross-linked network on the surface of the positive electrode and / or in the gaps between the positive electrode active materials; the cross-linked phosphonate polymer is formed by coating an unsaturated phosphonate polymerizable monomer on the surface of the positive electrode, or mixing an unsaturated phosphonate polymerizable monomer into a positive electrode slurry to form a electrode, and then completing in-situ polymerization and cross-linking during the electrode baking process; The unsaturated phosphonate polymerizable monomer comprises a phosphorus atom and two or more unsaturated carbon-carbon bonds, and at least one carbon atom in one unsaturated carbon-carbon bond is directly connected to the phosphorus atom.

2. The polymer-modified positive electrode plate according to claim 1, characterized in that: The unsaturated carbon-carbon bond further includes a substituent; the substituent is a halogen.

3. The polymer-modified positive electrode plate according to claim 1, characterized in that: The structure of the unsaturated phosphonate polymerizable monomer is shown in Formula I: Formula I , Wherein, R1 and / or R2 contain at least one unsaturated carbon-carbon bond.

4. The polymer-modified positive electrode plate according to claim 3, characterized in that: At least one unsaturated carbon-carbon bond is at the terminal end of R1 and / or R2.

5. The polymer-modified positive electrode plate according to claim 3, characterized in that: R1 and / or R2 may also contain non-carbon-carbon unsaturated bonds.

6. The polymer-modified positive electrode plate according to claim 5, characterized in that: The non-carbon-carbon unsaturated bond is a polar functional group; the polar functional group includes at least one of an amide group, a ketone group, and an ester group.

7. The polymer-modified positive electrode plate according to claim 5 or 6, characterized in that: At least one carbon atom C at both ends of an unsaturated carbon-carbon bond is connected to at least one atom X at both ends of a non-carbon-carbon unsaturated bond; the connection mode is CX or CYX; wherein Y is any one of O, S, CR3R4, NR5, PR6, PR7R8R9, wherein R3, R4, R5, R6, R7, R8, and R9 are independently selected from any one of hydrogen, halogen, alkyl, and halogenated alkyl.

8. The polymer-modified positive electrode plate according to claim 3, characterized in that: At least one unsaturated carbon-carbon bond in R1 and / or R2 further includes a substituent; the substituent is a halogen.

9. The polymer-modified positive electrode plate according to claim 3, characterized in that: At least one unsaturated carbon-carbon bond in R1 and / or R2 further includes a halogen substituent; the unsaturated carbon-carbon bond is on the terminal group.

10. The polymer-modified positive electrode plate according to claim 3, characterized in that: The R1 and / or R2 is selected from at least one of hydrogen, alkanes, alkenes or alkynes with or without halogen substituents, ketone groups, ester groups, amides and isocyanates.

11. The polymer-modified positive electrode plate according to claim 3, characterized in that: The R1 and / or R2 are selected from -H, -CH=CH2, -CH2F, -COCH3, -CONH2, -NHCOCH2CH=CH2, -NHCOCH=CH2, -NHCOCH2CH2CH=CH2, -NHCOCH2CBr=CH2, -NHCOCH(Br)CH=CH2, -COCH=CHF, -COCH=CH2, -CH=CHCH(Cl)CHCl2, -CH=CHCH2CH3, -CONHCH2CH2OOCC(CH3)=CH2, -CONHCH2CH2OOCC(CH3)=CHF, -CONHCF=CHOOCCHCH3CH3.

12. The polymer-modified positive electrode plate according to any one of claims 1 to 4, characterized in that: The unsaturated phosphonate polymerizable monomer is selected from , , , , , At least one of .

13. The polymer-modified positive electrode plate according to claim 3, characterized in that: The cross-linked phosphonate polymer is formed by in-situ polymerization and cross-linking of an unsaturated phosphonate polymerizable monomer of formula I; or by in-situ polymerization and cross-linking of an unsaturated phosphonate polymerizable monomer of formula I with other unsaturated phosphonate monomers, wherein the other unsaturated phosphonate monomers refer to unsaturated phosphonate monomers not within the scope of formula I.

14. The polymer-modified positive electrode plate according to claim 1, characterized in that: The mass ratio of the cross-linked phosphonate polymer, the positive electrode active material, the positive electrode binder, and the conductive additive in the positive electrode plate is (0.01~10):(80~99):(0.1~10):(0.1~10); the mass percentage of the cross-linked phosphonate polymer in the polymer-modified positive electrode plate is 0.01~10%.

15. The polymer-modified positive electrode plate according to claim 14, characterized in that: The mass percentage of the cross-linked phosphonate polymer in the polymer-modified positive electrode plate is 0.01-3%.

16. A method for preparing the polymer-modified positive electrode sheet according to any one of claims 1 to 15, characterized in that: The method comprises the following steps: S1: adding an unsaturated phosphonate polymerizable monomer and an initiator to a positive electrode plate for modification by blending or coating, wherein the positive electrode plate comprises a positive electrode active material, a positive electrode binder and a conductive additive; S2: Bake the positive electrode plate mixed or coated with unsaturated phosphonate polymerizable monomer and initiator, and make the unsaturated phosphonate polymerizable monomer undergo in-situ cross-linking polymerization by thermal initiation, the baking temperature is 30~80℃, and the baking time is 1~24 hours, so that the unsaturated phosphonate polymerizable monomer is fully polymerized to obtain a cross-linked phosphonate polymer, and a 3D cross-linked network is formed on the surface of the positive electrode plate and / or in the gaps of the positive electrode active material.

17. The method according to claim 16, characterized in that In step S1, the amount of the initiator added is 0.1-5% of the mass of the unsaturated phosphonate polymerizable monomer; In step S2, the baking temperature is 50-70° C., and the baking time is 10-15 hours.

18. The method according to claim 17, characterized in that The amount of the initiator added in step S1 is 0.5-1.5% of the mass of the unsaturated phosphonate polymerizable monomer.

19. A secondary lithium battery comprising the polymer-modified positive electrode sheet according to any one of claims 1 to 15.

Citation Information

Patent Citations

  • Solid-state battery and preparation method and application thereof

    CN111710817A

  • All-solid-state lithium battery and preparation method thereof

    CN112366292A